2015
DOI: 10.1080/07347332.2014.977417
|View full text |Cite
|
Sign up to set email alerts
|

What Explains the Intention to Be Physically Active in Cancer Patients? Different Determinants for Active and Insufficiently Active Patients

Abstract: In a qualitative elicitation study with 61 cancer patients, a broad range of attitudes toward physical activity could be obtained, especially negative attitudes among insufficiently active patients. Based on these results, a second quantitative study was conducted; 64 patients [40 men; 42% insufficiently active (<150 minutes/week)] completed a Theory of Planned Behavior (TPB) questionnaire. Regression analyses revealed that different variables of the TPB are relevant for explaining the intention to exercise fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Our findings highlight important subgroup-specific differences in exercise barriers, facilitators, and motivators, which can be used to adapt intervention delivery approaches for cancer survivors. Notably and consistent with previous research [38][39][40], positive survivor beliefs regarding the general health and cancer-specific benefits of exercise consistently associated with more sources of exercise motivation, more reported ways to facilitate exercise, and higher interest in participating in local exercise support services. Together, these findings suggest that support interventions designed to improve survivors' perceptions towards the benefits of exercise may play an important role in improving exercise engagement in cancer survivors.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings highlight important subgroup-specific differences in exercise barriers, facilitators, and motivators, which can be used to adapt intervention delivery approaches for cancer survivors. Notably and consistent with previous research [38][39][40], positive survivor beliefs regarding the general health and cancer-specific benefits of exercise consistently associated with more sources of exercise motivation, more reported ways to facilitate exercise, and higher interest in participating in local exercise support services. Together, these findings suggest that support interventions designed to improve survivors' perceptions towards the benefits of exercise may play an important role in improving exercise engagement in cancer survivors.…”
Section: Discussionsupporting
confidence: 85%
“…All variables of the TPB were developed according to Ajzen's and Fishbein's guidelines (Ajzen, 2002;Fishbein & Ajzen, 2011) and are based on previous studies (Ungar et al, 2015;Ungar et al, 2016).…”
Section: Variables Of the Tpbmentioning
confidence: 99%
“…Several studies regarding psychosocial determinants of PA in CPS have shown that attitude, subjective norms and perceived behavioral control (constructs of the Theory of Planned Behavior (TBP)) predict intention to engage in PA and PA behavior [68, 76–85]. Pinto and Ciccolo [77] reported that self-efficacy and outcome expectations (constructs of Social Cognitive Theory (SCT)) were important determinants of PA behavior.…”
Section: Step 2: Program Outcomes and Objectivesmentioning
confidence: 99%